Marriage Guardianship for Adopted Children in Akeguraci Village: A Perspective of Fiqh Munakahat - Killian, Nursinita; Abubakar, Fatum; Jamil, Jamaliah; Harwis, Harwis (IAIN Manado, 2024)
This study aims to analyze the practice of adoptive siblings acting as marriage guardians for adopted children in Akeguraci Village from the perspective of fiqh munakahat. A marriage guardian (wali) is one of the essential pillars of marriage; without a guardian, a marriage is deemed invalid, especially for individuals who have not yet reached the age of accountability (mukallaf). There are two types of marriage guardians: guardians by lineage (wali nasab) and judicial guardians (wali hakim). In Akeguraci Village, there is a case where the marriage guardian did not fulfill the essential requirements for guardianship. The guardian in this marriage was the biological son of the adoptive father. The mistake in the guardianship of the adopted child's marriage, performed by the adoptive sibling, occurred because the biological father refused to act as the guardian. This qualitative research collects field data through observation and interviews to uncover the practice of adoptive siblings acting as marriage guardians in Akeguraci Village. The findings reveal two main points: first, the practice of having the biological son of the adoptive father serve as the marriage guardian occurred because the biological father was unwilling to officiate the marriage, citing the child’s adoption at a young age as the reason. Second, from the perspective of fiqh munakahat, the marriage of an adopted child officiated by an adoptive sibling is invalid, as there is no lineage (nasab) relationship between the adopted child and the adoptive sibling.Al-Jaziri, A. (1996). Kitab al-Fiqh ’ala Madzahib al-’Arba’ah. Dar al-Fikr.Al-Qurthuby. (1993). Jami’ li Ahkam al-Qur’an. Dar al-Kutub al-Ilmiyyah.Anwar, M. (1990). Fiqih Islam Mu’amalah, Munakahat, Fara’id, dan Jinayah. Al-Ma’arif.Ar-Rifai, M. N. (2012). Ringkasan Tafsir Ibnu Katsir Jilid 3. Gema Insani.Assagaf, M. (2023). Pertimbangan Hakim pada Perkara Dispensasi Nikah di Lingkungan Pengadilan Agama Tutuyan. Al-Mujtahid: Journal of Islamic Family Law, 3(1), 36–50.Az-Zuhaili, W. (2011). Fiqih Islam wa Adillatuhu. Gema Insani Press.Dahlan, R., & Reza, A. (2022). Adoption of Children and Its Relationship With Guardianship in a Review of Islamic Law and Legislation in Indonesia (Case Study At the Palu Religious Court Class 1 a). Jurnal Ilmu Hukum Dan Ekonomi Islam, 4(1), 1–23.Djamal, A. (2000). Perkawinan di Indonesia. Raja Grafindo Persada.Hafid. (2022). Wali Nikah Anak Angkat dalam Perkawinan yang Tidak Diketahui Orang Tuanya: Studi Komparatif Fiqih Syafi’i dan Kompilasi Hukum Islam. Al-Qadlaya : Jurnal Hukum Keluarga Islam, 1(2), 51–58. https://doi.org/10.55120/qadlaya.v1i2.607Harwis, H., Killian, N., & Husna, H. (2024). Wife’s Permission as a Polygamy Requirement in The Perspective of Islamic Law and Positive Law. Proceeding International Conference Khairun University, 1(1), 85–91.Hidayah, F. I. (2014). Diskursus Hukum Islam di Indonesia Tentang Perwalian Perkawinan Anak Angkat. Isti’dal: Jurnal Studi Hukum Islam, 1(1), 75.Hosen, I. (1971). Fiqh Perbandingan Dalam Masalah Nikah, Thalaq, Rujuk, dan Hukum Kewarisan Jilid 1. Balai Penerbitan & Perpustakaan Islam Yayasan Ihya ’Ulumiddin Indonesia.Insani, N., Beddu, S., Rahman, R., Arpin, A., & Samuri, M. A. A. (2024). Judicial Considerations in Child Marriage Dispensations: An Empirical Study of the Gorontalo Religious Court. Jurnal Ilmiah Al-Syir’ah, 22(1), 41–52. https://doi.org/http://dx.doi.org/10.30984/jis.v22i1.2066Ismail, N. Z., Abubakar, F., Sanmas, A., Fadhly, M., & Killian, N. (2024). Review of Islamic Marriage Law Regarding Kafaah Sayyid-Syarifah Marriages in the Ternate Arab Community. Al Hakam: The Indonesian Journal of Islamic Family Law and Gender Issues, 4(2), 136–156. https://doi.org/https://doi.org/10.35896/alhakam.v4i2.843Jalal. (2024). Interview with Akeguraci Religious Leader on August 11, 2024.Junus, M. (1964). Perkawinan dalam Islam. Bulan Bintang.Kelib, A. (1990). Hukum Islam. PT. Tugu Muda Indonesia.Liao, M. (2016). Factors affecting post-permanency adjustment for children in adoption or guardianship placements: An ecological systems analysis. Children and Youth Services Review, 66, 131–143. https://doi.org/https://doi.org/10.1016/j.childyouth.2016.05.009Manan, A. (2006). Aneka Masalah Hukum Perdata Islam di Indonesia. Kencana.Martoredjo, A. I. A. (2021). Status Nasab Anak Lahir Di Luar Perkawinan Perspektif Hukum Islam Dan Hak Asasi Manusia. Al-Mujtahid: Journal of Islamic Family Law, 1(1), 1. https://doi.org/10.30984/jifl.v1i1.1640Nur Hadi, M., & Khiyaroh, K. (2020). Modin dan Otoritasnya: Studi Kasus Larangan Kawin Hamil di Kelurahan Temas Kota Batu. YUDISIA : Jurnal Pemikiran Hukum Dan Hukum Islam, 11(1), 33. https://doi.org/10.21043/yudisia.v11i1.7352Ramulyo, M. I. (1996). Hukum Perkawinan Islam. Bumi Aksara.Rolock, N., White, K., Blakey, J. M., Ocasio, K., Korsch-Williams, A., Flanigan, C., Bai, R., Faulkner, M., Marra, L., & Fong, R. (2023). Living apart after adoption or guardianship: Perspectives of adoptive parents and guardians. Children and Youth Services Review, 153, 107107.Rustamil. (2024). Interview with Adoptive Sibling in Akeguraci Village on August 10, 2024.Sarida. (2024). Interview with Akeguraci Resident on August 11, 2024.Soekito, S. widoyati W. (1989). Anak dan Wanita Dalam Hukum. LP3ES.Soemiyati. (2007). Hukum Perkawinan Islam dan Undang-Undang Perkawinan (Undang-undang No. 1 Tahun 1974 Terntang Perkawinan). Liberty.Subeitan, S. M., Isima, N., & Alhabsyi, M. S. (2021). Dinamika Pengangkatan Anak di Indonesia. Al-Mujtahid: Journal of Islamic Family Law, 1(1), 59–68. https://doi.org/http://dx.doi.org/10.30984/jifl.v1i1.1617Sukari, A. (2020). Dampak Sosio-Religius Tentang Waris Anak Angkat Dan Para Pihak Perspektif Kompilasi Hukum Islam. In YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam (Vol. 11).Syahjuan, Y. A., Abubakar, F., & Alhadar, M. (2022). Keterlibatan Orang Tua dalam Rumah Tangga Anak di Kelurahan Guraping Kecamatan Oba Utara. Indonesian Journal of Shariah and Justice (IJSJ), 2(2), 253–274. https://doi.org/https://doi.org/10.46339/ijsj.v2i2.41Tamrin. (2024). Interview with Biological Father in in Akeguraci Village on August 10, 2024.Usman. (2024). Interview with Adoptive Father in Akeguraci Village on August 10, 2024.Yusuf, M. (2017). Metode Penelitian: Kuantitatif, Kualitatif, dan Penelitian Gabungan. Kencana.Zahara, F., & Sukiati, S. (2024). The Dynamics of Adoptive Fathers as Marriage Guardians in Contemporary Studies. Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 11(1), 33–48. https://creativecommons.org/licenses/by-sa/4.0/